IMPROVING THE STUDENTS’ WRITING ACHIEVEMENT IN REPORT TEXT THROUGH RUNNING DICTATION STRATEGY AT THE TENTH GRADERS OF IPA 5 MAN 3 KEDIRI IN 2016/2017 ACADEMIC YEAR - nizarudin, wahyu (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 1 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Considering some difficulties of foreign language learners’ experience especially in writing and their achievement in writing class, the researcher decided to do this study whether Running Dictation Strategy can improve students’ achievement of the tenth Grade students of MAN 3 Kediri. This study used qualitative design while Classroom Action Research (CAR) as the approach. This study was conducted in the tenth grade students of Science 5 Program. There were 36 students, 14 male students and 22 female students. To know the result of students’ activity the researcher used observation checklist, field note, and questionnaire. Meanwhile, to know the improvement of the achievement the researcher used test and observed the result of test by computing the mean and the percentage of classroom success. The result of the study showed that the students were more active and more interested in writing activity. In the cycle I, only50% students could achieve the criteria of success. In the cycle II, 92,10% students could achieve the criteria of success. It can be concluded that Running Dictation Strategy is one of Dictation strategy that can improve students’ achievement in writing.